Internet of Things Oxygen Reduction Potential Sensor for Oil Pollution Detection - Taufek, Nur Farina; Soon Chin Fhong (Evolution in Electrical and Electronic Engineering, 2023)
Oil pollution is one of the disasters that occur by the human being in Malaysia and globally. It destroys the river systems and terrestrial habitat daily especially the location of the facility, the terminal, and the transportation. The main objective of this work is to develop and design an Internet of Things (IoT) oxygen reduction potential sensor that can monitor oil spills and alert the authorized person when spills happen. The system consists of an oxidation-reduction potential sensor (ORP) to measure the sanitizer’s effectiveness in water. An Arduino UNO acts as a microcontroller in this system while the Wi-Fi module (ESP8266-01) is to send data from the microcontroller to the Blynk application. The Internet of Things (IoT) is a network of both electrical and internet-connected computers. This system can be linked over the Internet, allowing users to view the data from it and display real-time data of the oil spill to the user’s smartphone through the cloud dashboard Blynk application. This is necessary to provide rapid monitoring of oil spill occurrences. The proposed system is developed to rapidly monitor the abnormal changes in water quality.